The Role of Inequality in Climate-Poverty Debates - Tschakert, Petra (World Bank, Washington, DC, 2016)
There is no doubt that the poorest people are already and will continue to be most severely impacted by climatic changes, including shifting trends as well as more frequent and severe extreme events. Yet, new insights on the dynamics and distribution of poverty point to the need to comprehend where the poor and poorest are, how they are poor, and why their poverty constrains their abilities to cope with and adapt to occurring and predicted changes. This paper draws on a diverse and growing literature on climate change and poverty to argue that uneven power relations more so than exposure and sensitivity to climatic hazards make the poor and disadvantaged distinctly more vulnerable than more affluent, privileged, and powerful groups and individuals. Further, climatic stressors and climate change as well as climate policies, often entangled with social exclusion and institutional neglect, compound the issue of poverty and exacerbate human precariousness, hence acting as a threat multiplier. The paper compares different approaches to assessing poverty, and explores structural processes and power dynamics that drive or perpetuate inequalities. The paper also investigates how the currently nonpoor may become transient or chronic poor, how climate change may exacerbate poverty traps, and how interventions to curb emissions and multidimensional poverty may be tackled to pursue climate-resilient development pathways.